PENGEMBANGAN PERMAINAN MONOPOLI DALAM PEMBELAJARAN BERDIFERENSIASI UNTUK MENERAPKAN PROFIL PEMBELAJAR PANCASILA SISWA SEKOLAH DASAR NEGERI 173518 SILITONGA - Rezeki, Ulfa Sari; Seriana, Sabda; Putri, Nurhaliza (Universitas Quality, 2024)
Character education, especially in understanding and applying Pancasila values, is an important aspect in forming the character of elementary school students in Indonesia. However, conventional learning approaches are often ineffective in attracting students' interest and understanding of these values. Therefore, developing the Monopoly game as a differentiated learning medium to implement the Pancasila Student Profile is important to increase the effectiveness of learning Pancasila values in elementary schools. The aim of this research is to develop a monopoly game that can be used in differentiation learning to strengthen the Pancasila Student Profile of elementary school students. Specifically, the objectives of this research are (1) identifying students' learning needs in understanding and applying Pancasila values in differentiated classes (2) designing a monopoly game that suits the learning needs and profile of Pancasila students (3) testing the effectiveness of the monopoly game in improving understanding and application of Pancasila values to elementary school students. This research method uses the ADDIE (analysis, design, development, implementation, evaluation) approach in developing the monopoly game as a learning medium. Research steps include analysis of student needs and characteristics, monopoly game design, development of game prototypes, implementation in learning, evaluation of effectiveness. The research method involves collecting qualitative and quantitative data with tests, questionnaires, observations, and interviews with students and teachers.